2020
DOI: 10.1111/cas.14685
|View full text |Cite|
|
Sign up to set email alerts
|

Steroid receptor coactivator‐1 enhances the stemness of glioblastoma by activating long noncoding RNA XIST/miR‐152/KLF4 pathway

Abstract: Glioblastoma (GBM) recurrence is attributed to the presence of therapy‐resistant glioblastoma stem cells. Steroid receptor coactivator‐1 (SRC‐1) acts as an oncogenic regulator in many human tumors. The relationship between SRC‐1 and GBM has not yet been studied. Herein, we investigate the role of SRC‐1 in GBM. In this study, we found that SRC‐1 expression is positively correlated with grades of glioma and inversely correlated with glioma patient’s prognosis. Steroid receptor coactivator‐1 promotes the prolifer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(9 citation statements)
references
References 74 publications
0
9
0
Order By: Relevance
“…This activity resulted in the inhibition of the proliferation, migration, and invasion of glioblastoma stem cells, and promoted their apoptosis (62). In line with Ma's study, recent research conducted by Gong showed that the miR-152/KLF4 axis enhanced the stemness of glioblastoma cells (63). The authors further discovered that the low expression of miR-152 was caused by activation of lncRNA X-inactive specific transcript (XIST) by steroid receptor coactivator-1 (SRC1).…”
Section: Glioblastomamentioning
confidence: 65%
“…This activity resulted in the inhibition of the proliferation, migration, and invasion of glioblastoma stem cells, and promoted their apoptosis (62). In line with Ma's study, recent research conducted by Gong showed that the miR-152/KLF4 axis enhanced the stemness of glioblastoma cells (63). The authors further discovered that the low expression of miR-152 was caused by activation of lncRNA X-inactive specific transcript (XIST) by steroid receptor coactivator-1 (SRC1).…”
Section: Glioblastomamentioning
confidence: 65%
“…Wang et al (42) have shown that KLF4 promotes spare respiratory capacity of human GBM cells by inducing mitochondrial fusion. Gong et al revealed that SRC-1 promotes GBM stemness through KLF4 activation (29). Wang et al found that HIF1/2a-induced KLF4 expression enhances the malignant progression of GBM by promoting stemness and cell cycle arrest (42).…”
Section: Discussionmentioning
confidence: 99%
“…KLF4 is a core component of the pluripotency transcription network that is involved in the regulation of cell cycle following DNA damage ( 28 ). A recent study has proved that KLF4 can be targeted by lncRNA XIST/miR-152 in regulating stemness in GBM ( 29 ). In this study, a screened prognosis-associated differentially expressed RNA (DER), CHRM3-AS2, was analysed in glioma.…”
Section: Introductionmentioning
confidence: 99%
“…Additionally, SRC-1 was shown to elevate glioblastoma stemness by modulating the XIST/miR-152/KLF4 axis, which provided a new diagnostic and therapeutic biomarker for glioblastomas (Fig. 3 F) (Gong et al 2021 ).
Fig.
…”
Section: Xist In Various Human Tumorsmentioning
confidence: 99%